2005
DOI: 10.1534/genetics.104.035238
|View full text |Cite
|
Sign up to set email alerts
|

Natural Allelic Variation in the Temperature-Compensation Mechanisms of the Arabidopsis thaliana Circadian ClockSequence data from this article have been deposited with the EMBL/GenBank Data Libraries under accession nos. AY685131 and AY685132.

Abstract: Temperature compensation is a defining feature of circadian oscillators, yet no components contributing to the phenomenon have been identified in plants. We tested 27 accessions of Arabidopsis thaliana for circadian leaf movement at a range of constant temperatures. The accessions showed varying patterns of temperature compensation, but no clear associations to the geographic origin of the accessions could be made. Quantitative trait loci (QTL) were mapped for period and amplitude of leaf movement in the Colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
206
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(221 citation statements)
references
References 45 publications
14
206
1
Order By: Relevance
“…The lhy mutant, therefore, has a shorter period than cca1 (Student's t test, P < 0.01) at 278C, supporting a role for LHY in the temperature compensation mechanism. This was suggested previously by analysis of natural genetic variation (Edwards et al, 2005), as LHY was noted as a candidate gene for the temperature-specific QTL PerCv1a and PerCola. At 128C, the period of the wild type (23.3 h) differed from that of lhy (21.6 h) by 1.7 h. In cca1, however, the rhythm of CAB:LUC expression was dampened ( Figure 5), and the period difference between the wild type (23.3 h) and cca1 (20.0 h) was 3.3 h. This temperature-dependent shortening of the circadian period and the reduction in rhythm robustness almost phenocopied the effect of gi-11 at 128C (Figures 1 and 2).…”
Section: Lhy and Cca1 Contribute Differentially To Temperature Compensupporting
confidence: 64%
See 2 more Smart Citations
“…The lhy mutant, therefore, has a shorter period than cca1 (Student's t test, P < 0.01) at 278C, supporting a role for LHY in the temperature compensation mechanism. This was suggested previously by analysis of natural genetic variation (Edwards et al, 2005), as LHY was noted as a candidate gene for the temperature-specific QTL PerCv1a and PerCola. At 128C, the period of the wild type (23.3 h) differed from that of lhy (21.6 h) by 1.7 h. In cca1, however, the rhythm of CAB:LUC expression was dampened ( Figure 5), and the period difference between the wild type (23.3 h) and cca1 (20.0 h) was 3.3 h. This temperature-dependent shortening of the circadian period and the reduction in rhythm robustness almost phenocopied the effect of gi-11 at 128C (Figures 1 and 2).…”
Section: Lhy and Cca1 Contribute Differentially To Temperature Compensupporting
confidence: 64%
“…Within this region was the flowering-time gene GI. Sequencing GI from Ler and Cvi revealed a number of polymorphisms, two of which resulted in amino acid substitutions (Edwards et al, 2005). This, together with the period effects of the gi mutant (Park et al, 1999), confirmed GI as a strong candidate for a gene involved in the temperature compensation mechanism.…”
Section: Gi Plays a Critical Role In Maintaining Rhythmicity In Leaf mentioning
confidence: 73%
See 1 more Smart Citation
“…Considerable natural variation in temperature compensation has been described, and GI has been identified as a quantitative trait locus responsible for a substantial portion of that variation (Edwards et al, 2005). It seems likely that this clock property will prove amenable to forward and reverse genetic approaches.…”
Section: Entrainmentmentioning
confidence: 99%
“…In Arabidopsis, there is considerable circadian variation among natural genotypes (for examples, see Swarup et al, 1999;Edwards et al, 2005). There is a positive correlation between period length of a set of natural accessions and daylength encountered at latitude of origin of the accessions , which may indicate a selection of altered clock function under differing environmental conditions (temperature and daylength covary with latitude).…”
Section: Adaptive Fitness Conferred By Circadian Clocksmentioning
confidence: 99%